Computed‐tomography‐guided transforaminal intrathecal nusinersen injection in adults with spinal muscular atrophy type 2 and severe spinal deformity. Feasibility, safety and radiation exposure considerations. (28th April 2020) - Spiliopoulos, S.; Reppas, L.; Zompola, C.; Palaiodimou, L.; Papadopoulou, M.; Filippiadis, D.; Palialexis, K.; Ploussi, A.; Efstathopoulos, E.; Tsivgoulis, G.; Brountzos, E.
Abstract : Background and purpose: The purpose was to investigate our centre's experience on computed‐tomography‐guided (CT‐guided), transforaminal, intrathecal administration of nusinersen in adult subjects with spinal muscular atrophy (SMA) type 2 and severe spinal deformity. Method: This is a retrospective, single‐centre study investigating the feasibility and safety of CT‐guided, transforaminal, lumbar puncture for the intrathecal administration of nusinersen (Spinranza®; Biogen; Cambridge, MA, USA) in a cohort of adult subjects with SMA type 2, severe neuromuscular scoliosis and previous spinal surgery. Between January 2019 and October 2019, five male, adult, SMA type 2 subjects were eligible to be treated in our centre with nusinersen. The mean age of the patients was 31 ± 9 years (range 19–43 years). The study's outcome measures were technical success, adverse events and radiation exposure. Results: In total, four patients completed the four loading doses, whilst the fifth patient received only one loading dose; two patients also received their first maintenance doses. Overall, 20 consecutive transforaminal, intrathecal treatments were analysed. Technical success was 100% (20/20 intrathecal infusions). No adverse events were documented following the procedures. Mean dose–length product (DLP) value per injection was 665.4 ± 715.5 mGy*cm. Estimated mean effective dose per injection was 12.7 ± 12.9 mSv. Subgroup analysis between the chronologically first 10 versus subsequent 10 procedures demonstrated a clear trend towards less radiation exposure in the latter, although this difference did not reach statistical significance (DLP: 984.7 ± 903.3 vs. 436.7 ± 321.5 mGy*cm, P = 0.165; respectively). Conclusions: In this retrospective series, CT‐guided transforaminal access for intrathecal injection of nusinersen was proven feasible and safe. A decrease in radiation dose over time was noted. Protocols to minimize radiation exposure are essential.